Amortyzacja środków trwałych, a optymalizacja podatkowa - Furman, Łukasz (Przegląd Prawno-Ekonomiczny, 2013)
Streszczenie dostępne wyłącznie w języku angielskim: The article deals with the tax depreciation and the solutions, of which the payers of income tax can benefit. Among the methods, which were presented,there is the straight- line depreciation, the depreciation rate as individuals and higher depreciation rates. All these methods are classified as tax optimization, because they are financially profitable for companies.